Neutron-diffraction of hydrogen-rich molecules under high pressure - Massani, Bernhard (The University of Edinburgh, 2022)
A proton and an electron form the lightest element of the periodic table: Hydrogen. Despite the simplicity of this element and an ongoing research interest, surprisingly little is known about its solid phases and structures of hydrogen-rich compounds such as water, ammonia or methane. In the particular, high pressure phases of these compounds are poorly understood. The reason for this is of a two-fold nature; first and foremost, small, hydrogen-rich molecules have very complex phase diagrams - partially due to the quantum nature of hydrogen - and form a vast variety of crystal structures. And secondly, the only direct way of measuring the hydrogen positions in these crystal structures is neutron-diffraction. While very powerful in structure determination, this technique requires large sample volumes and, hence, the pressure range has been limited to below 40 GPa; until recently, neutron diffraction had to rely on large-volume pressure cell such as the Paris-Edinburgh-Press. The overall aim of this body of work was to overcome current pressure-limitations and the concomitant limitations in data quality using single-crystals in diamond anvil cells for neutron diffraction. This attempt has been successful and the data-reduction and correction procedure reported in this work are now being used at the Snap beamline at Sns (Oak Ridge National Laboratory). The original aim for the second half of this thesis was to use single-crystal neutron-diffraction to measure single-crystals of hydrogen (deuterium) and water. Due to the ongoing pandemic caused by Covid-19 and the restrictions to travel to Sns, this was not possible. Hence, the second half of this works tries to fill gaps in the knowledge of the high-pressure behaviour of water-gas compounds using existing techniques. In particular, studies on the water-nitrogen, water-ammonia and the water-ammonia-methane systems will be presented here.
Keywords: high-pressure crystal structures; H-H bond-length; high-pressure structures; deuterated potassium dihydrogen phosphate; gas hydrates under pressure